1999
DOI: 10.1207/s15327914nc3402_4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Marinating With Asian Marinades or Western Barbecue Sauce on PhIP and MeIQx Formation in Barbecued Beef

Abstract: Heterocyclic aromatic amines (HAAs), a group of chemicals formed during high-temperature cooking of meat and fish, are potent mutagens and are suspected to play a role in colorectal cancer. A recent study suggested that marinating meat may offer a way to reduce HAA formation. Hawaii's diverse ethnic populations, which are at various risks of colorectal cancer, often use traditional marinades when cooking meat. We compared the HAA content of beef steaks marinated overnight with teriyaki sauce, turmeric-garlic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 18 publications
2
22
0
Order By: Relevance
“…Here, in agreement with previous observations (Nerurkar et al, 1999; Salmon et al, 1997), the present study showed that marination before cooking had an overall reducing effect on HCA formation regardless of food items and cooking methods. Given that recipes for marinade varied across food items and cooking methods in this study, marinade might decrease HCA formation regardless of marinade type.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Here, in agreement with previous observations (Nerurkar et al, 1999; Salmon et al, 1997), the present study showed that marination before cooking had an overall reducing effect on HCA formation regardless of food items and cooking methods. Given that recipes for marinade varied across food items and cooking methods in this study, marinade might decrease HCA formation regardless of marinade type.…”
Section: Discussionsupporting
confidence: 94%
“…Given that recipes for marinade varied across food items and cooking methods in this study, marinade might decrease HCA formation regardless of marinade type. Interestingly, on the other hand, Nerurkar et al (1999) found a reducing effect of teriyaki and turmeric-garlic sauces on HCA formation but an enhancing effect of commercial honey barbecue sauce, suggesting that marinades vary in their effect on HCA formation. This would be unlikely to explain the lack of difference in HCA levels between marinated and non-marinated pan-fried salmon in the present study, however, because pan-fried pork marinated with a similar marinade showed a decrease in HCA formation over non-marinated samples.…”
Section: Discussionmentioning
confidence: 95%
“…Salmon, et al showed a 92-99% reduction in PhIP and a statistically insignificant increase in MeIQx with increased cooking time in marinated grilled chicken (Salmon et al 1997). Nerurkar, et al showed reduced PhIP and MeIQx in barbecued beef marinated with two different marinades, but increased HAA with a third marinade (Nerurkar et al 1999). Tikkanen et al tested four different marinades on grilled chicken and observed some increases and some decreases in mutagenic activity and in HAA levels measured by gas chromatography/mass spectrometry, depending on the marinade used and/or the cooking conditions (Tikkanen et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have examined other factors that might affect HAA formation, such as pretreatment with marinades (Tikkanen et al 1996;Salmon et al 1997;Nerurkar et al 1999), addition of vitamins, herbs or spices (Murkovic et al 1998;Balogh et al 2000), combination of fruit or vegetables with ground meat (Britt et al 1998;Kato et al 1998), and use of techniques such as microwave cooking (Felton et al 1994;Chiu et al 1998), convection roasting , or frequent turning of meat . Inherent characteristics of meats, such as animal source (Vikse and Joner 1993;Pais et al 1999;Olsson et al 2002), and fat and water content (Johansson and Jägerstad 1994) have also been considered, relative to the HAA levels that form in them when cooked.…”
Section: Introductionmentioning
confidence: 99%
“…This proposition is only tentative as contradictory results have been obtained in different studies. Marinating beef steaks with honey barbecue sauce produced a promoting effect on the formation of HAs [216], whereas a later study observed an inhibitory effect in fried pork chops premarinated with honey formulation [217]. It is thus probable that other food components and/or the way of increasing sugar levels have a modifying effect on the final outcome.…”
Section: Types and Concentrations Of Precursorsmentioning
confidence: 99%